61.6k views
5 votes
Solve for x.
4(1 – x) + 2 x = –3( x + 1)

User TomFuertes
by
5.5k points

2 Answers

0 votes

Answer: -7

Explanation:

4(1 – x) + 2 x = –3( x + 1)

Simplify the parentheses

4 - 4x + 2x = -3x - 3

Combine like terms

4 - 2x = -3x - 3

Subtract like terms on each side of the equal sign to isolate variable

x=-7

User Damir Tenishev
by
5.2k points
5 votes

Answer:

the answer is:

4 - 4x+ 2x = -3x -3

4 - 2x = -3x -3

4 + 3 = -3x +2x

7 = -x

x = (-7)

User Robert Zaremba
by
5.2k points